Larger and deeper ventricular lesions using a novel expandable spherical monopolar irrigated radiofrequency ablation catheter. (1st August 2019) - Kitamura, Takeshi; Hocini, Mélèze; Bourier, Felix; Martin, Ruairidh; Takigawa, Masateru; Frontera, Antonio; Thompson, Nathaniel; Cheniti, Ghassen; Vlachos, Konstantinos; Martin, Claire A.; Lam, Anna; Duchateau, Josselin; et al.
Abstract: Background: Radiofrequency (RF) ablation is an established treatment for ventricular tachycardia (VT). However, the inability of current RF catheters to address deep or large substrate may explain most of the clinical failures. Objectives: The aim of this study is to assess the efficacy and safety of ablation in the left ventricle (LV) in sheep using a novel 8‐Fr deflectable ablation catheter (Sphere‐9; Affera, Inc) with a 9‐mm expandable spherical monopolar irrigated RF tip vs a standard RF irrigated catheter (Biosense Webster, Diamond Bar, CA). The impact on tissue was assessed on local bipolar electrograms (from nine uniformly distributed mini surface electrodes and an internal central reference electrode), as well as on direct lesion measurement post mortem. Methods and Results: Eleven sheep underwent LV endocardial ablation in healthy tissue using the Sphere‐9 catheter (n = 6), or a conventional irrigated RF catheter (n = 5). Twenty lesions were created with the Sphere‐9 (current limit: 2.7 A; temp. limit: 60°C; irrigation: 30 mL/min; and duration: 60‐120 seconds). Local bipolar electrograms at the surface of the catheter disappeared during RF delivery in 17 of 20 (85%) lesions. The mean lesion volume was 1707 ± 771 mm 3 (length: 15.8 ± 3.3 mm; width: 11.6 ± 4.2 mm; and depth: 10.3 ± 2.9 mm). Twenty‐five lesions were created with a standard RF irrigated catheter (power control 35 W; irrigation: 30 mL/min; duration: 60 seconds; volume 537 ± 398 mm 3 ; length: 8.2 ± 2.3 mm; width: 5.2 ± 1.8 mm; and depth: 5.5 ± 2.4 mm). The novel spherical RF catheter created significantly larger lesions ( P  < .001 for measurements in all dimensions). There were no steam pops with the novel ablation catheter vs one with the conventional catheter. Conclusions: This novel spherical monopolar irrigated RF catheter creates lesions that are twice as large and deep as a standard irrigated RF catheter.